FEATURES OF THE USE OF REHABILITATION AND RECOVERY MEASURES IN THE TRAINING PROCESS OF QUALIFIED GYMNASTS - Trofimov, O.B.; Volkov, V.G.; Салаев, А.В.; Гатин, А.В. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to evaluate the effect and effectiveness of the use of the non-steroidal anti-inflammatory drug Amelotex, the chondroprotector Chondrogard, the synovial fluid replacement drug Rusvisk in the complex rehabilitation treatment of qualified gymnasts with post-traumatic prearthrosis of the knee joints. Methods and structure of the study. The scientific experiment involved eight qualified gymnasts who underwent a course of complex rehabilitation treatment from 2018 to 2020, including physiotherapy, exercise therapy, and massage. As part of this study, they were prescribed to take the non-steroidal anti-inflammatory drug Amelotex, the chondroprotector Chondrogard, and the hyaluronic acid preparation Rusvisk. Results and conclusions. As the study showed, the use of Amelotex, Chondrogard and Rusvisk in complex therapy contributes to the regression of pain in athletes, improves the static-dynamic function of the joints, increases sports activity and improves the quality of life.